A beautiful stroke?: A side note on the 75th anniversary of the spectacular death of the French organist and composer Louis Vierne (1870-1937) - Förch, Christian; Lemercier, Sophie; Hennerici, Michael G. (Cerebrovascular diseases, 2012)
The great French organist and composer Louis Vierne (1870-1937) died while performing an organ recital at Notre Dame cathedral in Paris - right in front of the console. This historical article provides insights into the biography of a highly talented musician who was challenged by disability and diseases throughout his career. A special focus is placed on the circumstances of Vierne’s remarkable death. Until now, both a primary cerebrovascular event and a ‘heart attack’ are discussed in reference books and encyclopedias as the immanent causes of death. From the perspective of a stroke neurologist, a reappraisal of Vierne’s medical history and the events that happened during his last concert is presented.
Gesehen am 09.04.2018
Keywords: Vierne, Louis -- 1870-1937